Computational Evaluation on Molecular Structure, Charge, NMR, Electronic (HOMO-LUMO) Properties, and Spectroscopic Profiling of Pioglitazone with Molecular Docking Studies - Segar, Soundhariya; Ravikumar, Keerthana; Jayasheela, Jayasheela; Sengeny, Periandy (Trends in Sciences, 2022)
The conformational study (PES-Potential Energy Scan) has been performed and a minimum energy conformer structure has been chosen for DFT (Density Functional Theory) exploration on Pioglitazone. Extensive quantum chemical calculations have been carried out to investigate the Fourier Transform Infrared (FTIR), Fourier Transform Raman (FT-RAMAN) investigation have been implemented by emerging DFT calculations based on the B3LYP level with 6-311 ++ G (d, p) basis set, which also helps to provide useful information about the structure of the title compound. The theoretical vibrational wavenumbers are compared with the experimental values. Natural bond orbital analysis has been carried out to explain the charge transfer (or) delocalization of charge due to the intra molecular interactions. NMR has been carried through the same method along with the GIAO method for assigning 1H and 13C chemical shifts. UV–Visible analysis has been done by taking DMSO as a solvent to obtain maximum absorption wavelength. Mulliken atomic charges and Natural population analysis to know electronegative and electropositive atoms in a molecule. Thus, this present study reports the structural, electrical, chemical, and biological activities of Pioglitazone. The molecular docking studies revealed that the title molecule can bind with the protein 1H5U a potential antidiabetic drug. HIGHLIGHTS The stable energy conformer and geometrical parameters were studied Theoretical data acquired using the DFT B3LYP/6–311++G (d,p) basis set was compared to FT-IR, FT-Raman, UV, and NMR results The molecule has a tiny energy gap according to HOMO-LUMO calculations Molecular docking studies suggested that the chemical may be utilized to treat diabetics GRAPHICAL ABSTRACT